Estudo da difusividade térmica em amostras cerâmicas de Ca2-xYxMnReO6 com x entre 0 e 0,3 - Almeida, Lucas Corrêa de (2013)
We studied compounds with ceramic structure of kind double perovskytes sorted with wide applicability in pressure transducers using electronic spins. A characterization of microstructure and thermal properties of these ceramics, produced by solid state reaction, was detailed. Analyzes of scattering electronic microscopy images provided us details and characteristics on the contours of grain and the distribution of the sizes of the same. The analysis of thermal diffusivity was made with use of laser Flash method which has the advantage to simultaneous determination of thermodynamic parameters , in short time interval. For the best our knowledge, it was first time that, the thermal diffusivity estimative of double perovskyte ceramic: 26 doped with yttrium (2−6) was estimated.